Copper and graphene work together to construct a three-dimensional skeleton thermal conductivity network to improve the thermal conductivity of the epoxy resin - Li, Shuo; Wu, Wei; Drummer, Dietmar; Wang, Yi; Lu, Zijian; Zhao, Xintong (Polymer Composites, 2023)
With the development of integrated circuits, the miniaturization and integration of electronic devices has become a development trend, and the demand for heat dissipation is also increasing. Graphene three-dimensional aerogels prepared from graphene has been widely used in the field of thermal management materials, but graphene aerogels also face the disadvantages of poor compatibility with resin matrix and high thermal resistance. In this study, a hybrid filler for depositing copper nanoparticles on the surface of graphene aerogel was prepared, and the hybrid aerogel filler showed excellent thermal conductivity, reduced the interfacial thermal resistance and contact thermal resistance, improved the interfacial thermal resistance with epoxy resin, and improved the interfacial compatibility. Under a low load of 2.5 wt%, the thermal conductivity of the prepared composite is as high as 2.09 Wm−1 K−1, which is about 11 times that of pure epoxy resin. It provides a simple idea for preparing high-thermal conductivity three-dimensional graphene epoxy resin composites with high thermal conductivity.
CRIS-Team Scopus Importer:2023-06-30
Keywords: composite material; epoxy resin; graphene aerogel; thermal conductivity